2023
DOI: 10.1021/acsami.3c02305
|View full text |Cite
|
Sign up to set email alerts
|

Enhance Mitochondrial Damage by Nuclear Export Inhibition to Suppress Tumor Growth and Metastasis with Increased Antitumor Properties of Macrophages

Abstract: Mitochondria-targeting damage has become a popular therapeutic option for tumor metastasis; however, its efficacy is limited by the adaptive rescue capacity of nuclei. There is an urgent need for a dual mitochondrial and nuclear targeting strategy that can also increase the antitumor capacity of macrophages. In this study, XPO1 inhibitor KPT-330 nanoparticles were combined with mitochondria-targeting lonidamine (TPP-LND) nanoparticles. The combination of nanoparticles with a 1:4 ratio of KPT and TL demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…According to previous studies, tumor metastasis is responsible for almost 90% of cancer-related deaths . Mitochondria produce nearly 95% of cellular ATP which actively supplies energy to encourage tumor development and metastasis. Besides, the high intratumoral oxygen consumption in cancer cells is due to strong aerobic respiration by the mitochondria, resulting in a hypoxia environment which further enhances tumor metastasis. , Hence, it has been confirmed that mitochondria participate throughout the tumor metastasis process, and mitochondrial-targeted damage has been developed as a popular strategy in the treatment of tumors . To date, more and more drugs have been developed to target mitochondria [e.g., triphenyl phosphonium, TPP + , Ru 2+ , and glycyrrhetinic acid (GA)] .…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, tumor metastasis is responsible for almost 90% of cancer-related deaths . Mitochondria produce nearly 95% of cellular ATP which actively supplies energy to encourage tumor development and metastasis. Besides, the high intratumoral oxygen consumption in cancer cells is due to strong aerobic respiration by the mitochondria, resulting in a hypoxia environment which further enhances tumor metastasis. , Hence, it has been confirmed that mitochondria participate throughout the tumor metastasis process, and mitochondrial-targeted damage has been developed as a popular strategy in the treatment of tumors . To date, more and more drugs have been developed to target mitochondria [e.g., triphenyl phosphonium, TPP + , Ru 2+ , and glycyrrhetinic acid (GA)] .…”
Section: Introductionmentioning
confidence: 99%
“…Through activation of PI3K/Akt/ Nrf2 pathway in GBM cells, VEGF produced by M2 GAMs promotes GBM cell stemness, proliferation, epithelialmesenchymal transition (EMT), and temozolomide resistance (51,53). VEGF downregulation caused by mitochondrial damage in tumor cells resulted in an increased rate of M1/M2 macrophages both in vivo and in vitro, which enhances the TAM effects to st r e n g t h e n t h e im m u n i t y t o a g a i ns t t u m o r s in th e microenvironment (54).…”
mentioning
confidence: 99%